2020
DOI: 10.1111/are.15045
|View full text |Cite
|
Sign up to set email alerts
|

Yucca schidigeraextract mediated the growth performance, hepato‐renal function, antioxidative status and histopathological alterations in Nile tilapia (Oreochromis niloticus) exposed to hypoxia stress

Abstract: The present study investigated influence of Yucca schidigera extract (Ys E) on the growth performance, hepato‐renal function, antioxidative status and histopathological alterations in Nile tilapia (Oreochromis niloticus) exposed to hypoxia stress. 120 Nile tilapia fish (42.39 ± 1.25 g) were distributed into four equal groups, where group (a) kept as a control group, group (b) supplied with YsE (8 mg/L water every 2 days), group (c) exposed to hypoxia after 2 weeks from the start of the experiment and group (d)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…Thus, this can decrease the toxic action of UIA on the gills and maintain gills' function and health. Interestingly, these results coincide with our findings of antioxidant activity of the mixture of QS/ YS and, hence, this protects gills' tissues from the inflammatory and degenerative influences of free radicals (Dawood et al, 2021;Elbialy et al, 2020;Elkaradawy et al, 2021). lymphocytes production improved the lysozyme activity, which modulated fish's immune status (Choi et al, 2013;Ruchin, 2020).…”
Section: Ta B L Esupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, this can decrease the toxic action of UIA on the gills and maintain gills' function and health. Interestingly, these results coincide with our findings of antioxidant activity of the mixture of QS/ YS and, hence, this protects gills' tissues from the inflammatory and degenerative influences of free radicals (Dawood et al, 2021;Elbialy et al, 2020;Elkaradawy et al, 2021). lymphocytes production improved the lysozyme activity, which modulated fish's immune status (Choi et al, 2013;Ruchin, 2020).…”
Section: Ta B L Esupporting
confidence: 90%
“…It has been reported that dietary QS extract can enhance the growth of common carp (Francis et al, 2002;Serrano, 2013;Serrano et al, 2000) and Nile tilapia (Elkaradawy et al, 2021;Francis et al, 2001). On the other hand, previous studies have demonstrated that YS can enhance the growth of catfish (Amoah et al, 2017;Güroy et al, 2014;Kelly & Kohler, 2003), carp (Dawood et al, 2021;Wang et al, 2020), Atlantic salmon (Gu et al, 2015), European seabass (Elkhayat et al, 2019), Pacific white shrimp (Yang et al, 2015) and Nile tilapia (Elbialy et al, 2020;Gaber, 2006;Njagi et al, 2017). In contrast, YS's dietary supplementation did not improve the FCR or growth of channel catfish (Tidwell et al, 1992).…”
Section: Ta B L Ementioning
confidence: 93%
See 1 more Smart Citation
“…Peng et al [28] reported that the dietary inclusion of condensed tannins (400 mg/kg) increased the hepatic CAT activity in Nile tilapia exposed to 10 h of hypoxia (1 mg/L dissolved oxygen). The dietary inclusion of Yucca schidigera extract as a source of PCs increased SOD and GPx activities in liver Nile tilapia exposed to hypoxia (2.2-2.6 mg/L dissolved oxygen) [2]. In the present study, the CAT activity was reduced by 44% in tilapia fed the control diet and exposed to hypoxia, while the CAT activity was reduced by 16% in tilapias exposed to hypoxia and fed CHM supplemented diet (Figure 1a); this possibly indicates that PCs from CHM promote cell homeostasis by increasing CAT activity via Nrf2 activation.…”
Section: Discussionmentioning
confidence: 97%
“…The high demand for fish and fishery products for human consumption worldwide has forced the aquaculture industry to develop modern aquaculture practices that are dependent on intensive farming systems [1]. This might cause temporary unstable conditions, such as changes in temperature, salinity, pH, ammonia nitrogen, and dissolved oxygen concentrations, which generates a stressful physiological environment for organisms (oxidative stress) [2]. In particular, the dissolved oxygen concentration is an important water quality criterion in intensive systems.…”
Section: Introductionmentioning
confidence: 99%